Analisis Pengaruh Variabel Makroekonomi terhadap Impor Bahan Baku di Indonesia Tahun 2020-2024 - Rizka Nur Hidayah; Reikha Habibah Yusfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Indonesia's raw material imports continue to increase from year to year, which shows the high dependence of the Indonesian industrial sector on raw materials from abroad. This study aims to analyze the influence of macroeconomic variables, namely inflation, money supply, interest rate, and exchange rate on raw material imports in Indonesia from January 2020 to December 2024. The data used is secondary data in the form of a monthly time series that comes from official publications of Bank Indonesia, the Central Statistics Agency, and the Ministry of Trade. The research analysis method uses the Ordinary Least Square (OLS) with the Newey-West HAC approach to overcome the problems of heteroscedasticity and autocorrelation. The results of the study show that inflation and the money supply have a positive and significant influence on raw material imports. Meanwhile, interest rates have a negative and significant influence on raw material imports. Meanwhile, in this study period, the exchange rate variable did not have a significant effect on the import of raw materials in Indonesia. From the results of the study, it can be concluded that raw material imports in Indonesia are influenced by domestic demand, economic liquidity, and interest rate policies compared to exchange rates.